Fostering the Moral Competence of University Teachers through Ethical Leadership: Exploring the Mediating Role of Psychological Empowerment - Naureen Saif, Nazia; Awan, Riffat-un-Nisa (UMT Education Review, 2023)
Leadership as a practice involves moral and ethical elements needed to run an organization justly and effectively. Empowered teachers who possess a strong morality can change the fabric of Higher education institutions. This study was designed to examine the mediating role of psychological empowerment in the relationship between ethical leadership of department heads (as perceived by university teachers) and teachers’ moral competence. It also strived to investigate gender differences in the relationship between ethical leadership of department heads and teachers’ moral competence and empowerment. An adopted questionnaire was used for data collection. The sample consisted of 265 teachers from five public sector universities in Punjab, Pakistan. Gender differences were explored through t-test. Pearson’s moment correlation coefficient was used to determine the relationship between ethical leadership of department heads and teachers’ moral competence. Structure Equation Modeling (SEM) was used for mediation analysis. The results revealed that leaders’ ethical behavior is positively related to teachers’ psychological empowerment and moral competence. It was also found that the ethical leadership practices of male and female department heads were the same. Simultaneously, there was no gender difference was found in teachers’ moral competence. SEM results indicated that all direct effects were significant, except for ethical leadership and moral competence. The indirect effect of leadership on moral competence through the mediation of psychological empowerment was found to be significant, which suggests complete mediation.